A 3D memristive chaotic system with conditional symmetry. (May 2022) - Wang, Ran; Li, Chunbiao; Kong, Sixiao; Jiang, Yicheng; Lei, Tengfei
Abstract: Based on the special structure of variable-boostable chaotic system VB24, a quadratic flux-controlled memristor is embedded for the construction of a 3D memristive chaotic system with conditional symmetry. Coexisting oscillations with conditional symmetry are confirmed systematically based on the bifurcation analysis and circuit verification. Two constants in the absolute value functions play the role of offset boosting, which modifies the distance between pairs of coexisting attractors separately in external and internal state space. Interestingly, any of two coexisting attractors with conditional symmetry could be symmetric or asymmetric. An analog circuit is designed to verify the coexisting oscillations as predicted. Highlights: A memristor-based 3-D variable-boostable chaotic system with conditional symmetry is derived. Two independent offset controllers are equipped for regulating the distance between any two conditional symmetric attractors. Circuit realization proves the above properties based on a memristor simulator.